Band 2 - Möller, Horst; Cubar'jan, Aleksandr O. (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2023)
This volume represents a contribution by the Commission to the commemoration of the end of the Second World War. In addition, the volume also provides information on projects that have been carried out under the supervision of the Commission, with financial support from the German government, and with the support of the Russian Academy of Sciences and the German and Russian archives involved. The appendix documents the new archive law of the Russian Federation of October 22, 2004, as well as the basic exchange of letters of 1997, which led to the formation of the Joint German-Russian Historical Commission.